European Welfare Production - Vogel, Joachim. author. aut Link
IV, 274 p.
Keywords: European Welfare Production is of interest to researchers in quality of life research, economists and political scientists interested in welfare regimes and comparative social welfare research, and administrators in social planning and social work. The aim of this book is to identify the variation in welfare regimes (distribution of responsibilities for welfare delivery between the labour market, the family and the welfare state) and the corresponding welfare outcome at the micro level. The research agenda of this report sets out from the tradition of the "social indicator movement", and recent regime research. Combining the data on `welfare production' provides insight into the way living conditions are monitored between the labour market, welfare state and family at national level. It also provides insight into the combined `welfare efficiency' of these institutions, with special focus on distributional features.